Revitalisasi Pendidikan Karakter Melalui Budaya Lokal - Ni’matu Sholikhah (KOLONI, 2023)
Character education is an important aspect in the formation of quality individuals in society. Local culture has great potential in supporting the formation of strong character in individuals. This article aims to explore the concept of revitalizing character education through the use of local culture as an effective learning tool. In an effort to increase this understanding, this article will discuss character education theory, the role of local culture in character education, and strategies for revitalizing character education through local culture. Keywords: revitalization, character education, local culture